Identification for Development : Zambia - World Bank Group (World Bank, Lusaka, 2016)
Zambia provides a distinctive case of national identity management. Even from before independence in 1964 the identity card has played a prominent role and by 2010 the National Registration Card (NRC) covered more than 83 percent of the population of 16 and above. At the same time civil registration (the registration of births, deaths,marriages, divorces and other vial events) has remained underdeveloped, inter alia because of a lack of utility perceived by many, poverty among large parts of the population and a centralized process anchored in the law of 1973. The country is now embarking on a reorganization of its civil registration operations and is on the brink of introducing a new national ID.This report of the World Bank's mission on its Identity Management Systems Analysis (IMSA) in Zambia should be seen against the backdrop of the rapid introduction of information and communication technology in all spheres of life, including in e-government and in the digital economy across the globe, and in Africa witness the theme of the 2016 World Economic Forum held in Rwanda. This report first starts with an analysis of the state-of-play in the domain of national identity management, which is its prime focus, in Chapter 3. It then moves on to an analysis of the policy, institutional and regulatory frameworks for delivering e-government and identity services in Chapter 4. Chapter 5 then presents an analysis of institutional demand for identity services, covering some major public and private sector actors, such as Zambia's Revenue Authority, Bank of Zambia and the Ministry of Community Development and Social Welfare, and private sector actors such as banks, insurance companies and MNOs. The report's last section in Annex 6 presents conclusions and recommendations.